Analisis Usahatani Nanas Madu di Desa Sukajadi Kecamatan Kuala Cenaku Kabupaten Indragiri Hulu - Yuslizar; Khairudin; Khairizal (Jurnal Indragiri Penelitian Multidisiplin, 2025)
This study aims to analyze the cultivation techniques, farmer profiles, costs, production, and income of Honey Pineapple farmers using a survey method. The location was chosen purposively, and samples were collected using a simple random sampling technique. The results showed that Honey Pineapple cultivation techniques include seed preparation, planting land preparation, planting, maintenance (replanting, weeding, fertilization), harvesting, and post-harvest. In general, the farmers are aged 15-54 years (80%), have more than 5-7 years of farming experience (80%), have an education level of >6 ≤ 9 years (70%), and have 3-4 family dependents (50%). The average fixed cost is Rp. 530,719 per Cultivated area per year, the variable cost is Rp. 25,356,000 per Cultivated area per year, so the total cost is Rp. 25,886,719 per Cultivated area per year. The average production produced by farmers is 4,810.56 kg per Cultivated area per year and has increased to 6,013.2 kg per Cultivated area per year. In the first year, gross income was Rp. 24,052,800 per Cultivated area per year, net income was -Rp. 1,833,919 per Cultivated area per year, and family income was Rp. 5,000,550 per Cultivated area per year with an RCR of 0.92. In the second year, gross income became Rp. 30,066,000 per Cultivated area per year, net income was Rp. 24,071,281 per Cultivated area per year, and family income was Rp. 28,133,750 per Cultivated area per year with an average RCR of 5.40.